2018
DOI: 10.1002/pssa.201700758
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Imaging of Dislocation Expansion in FZ‐Si Seeds During Temperature Ramp Heating Process

Abstract: The impact of the thermal field in a directional solidification furnace on the generation and propagation of dislocations is investigated in intrinsic floating zone single crystal silicon.Seeds with different crystallographic orientations are wire-cut from mono-crystalline wafers and dislocation sources are solely left at the edges. Thermal annealing experiments are carried out in situ at the European synchrotron radiation facility and the evolution of the silicon crystalline quality is studied by X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…During the heating segment of the experimental procedure, dislocations appear in the sample as seen before [36] and remain in the seed kept after partial melting. During solidification, these dislocations develop, usually along the growth direction and can encounter grain boundaries.…”
Section: Grain Competition and Associated Strain Buildingmentioning
confidence: 99%
“…During the heating segment of the experimental procedure, dislocations appear in the sample as seen before [36] and remain in the seed kept after partial melting. During solidification, these dislocations develop, usually along the growth direction and can encounter grain boundaries.…”
Section: Grain Competition and Associated Strain Buildingmentioning
confidence: 99%
“…It was shown by Tsoutsouva et al (2018) that at a temperature of 1373 K a horizontal slip system is activated for a sample of the same orientation as sample B and with the same crucible arrangement and comparable temperature conditions. It was concluded that this slip system initiates from the sample side zones that are damaged during preparation and is activated by an external force acting on the sample surface, i.e.…”
Section: Heating and Meltingmentioning
confidence: 99%
“…Another main originality of the experimental configuration we use is that several Laue patterns or topographs are recorded during a solidification experiment [45,46,71]. Then, it is possible to obtain sequences showing the evolution with time of the Laue pattern and of the topographs during the development of the grains.…”
Section: Dynamic Evolutionmentioning
confidence: 99%
“…Before presenting results on strain building, it is important to specify that during the heating segment of the experimental procedure, dislocations appear in the sample as described in [71] and remain in the seed kept after partial melting. During solidification, these dislocations develop, usually along the growth direction and can encounter grain boundaries.…”
Section: Strain Building During Growthmentioning
confidence: 99%